1998
DOI: 10.3102/10769986023004291
|View full text |Cite
|
Sign up to set email alerts
|

Improved Type I Error Control and Reduced Estimation Bias for DIF Detection Using SIBTEST

Abstract: One emphasis in the development and evaluation of SIBTEST has been the control of Type I error (false flagging of non-differential item functioning [DIF] items) inflation and estimation bias. SIBTEST has performed well in comparative simulation studies of Type I error and estimation bias relative to other procedures such as the Mantel-Haenszel and Logistic Regression. Nevertheless it has for a minority of cases that might occur in applications displayed sizable Type I error inflation and estimation bias. A vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 12 publications
0
40
1
Order By: Relevance
“…There are a number of methods available for detecting uniform DIF, including the Mantel-Haenszel test (MH), logistic regression (LR), and SIBTEST (Millsap & Everson, 1993;Shealy & Stout, 1993). Several studies have demonstrated the effectiveness of these methods under a wide variety of simulated conditions (e.g., Rogers & Swaminathan, 1993;Roussos & Stout, 1996;Jiang & Stout, 1998;Narayanan & Swaminathan, 1994). While collectively this work identified some minor differences in the effectiveness of these DIF detection methods, generally speaking they were found to perform similarly well in most situations.…”
mentioning
confidence: 65%
“…There are a number of methods available for detecting uniform DIF, including the Mantel-Haenszel test (MH), logistic regression (LR), and SIBTEST (Millsap & Everson, 1993;Shealy & Stout, 1993). Several studies have demonstrated the effectiveness of these methods under a wide variety of simulated conditions (e.g., Rogers & Swaminathan, 1993;Roussos & Stout, 1996;Jiang & Stout, 1998;Narayanan & Swaminathan, 1994). While collectively this work identified some minor differences in the effectiveness of these DIF detection methods, generally speaking they were found to perform similarly well in most situations.…”
mentioning
confidence: 65%
“…Some researchers have found that SIBTEST and Rasch methods are comparable in terms of identifying DIF items and in terms of type 1 error (Narayanan & Swaminathan, 1994;Rogers & Swaminathan, 1993;Roussos & Stout, 1996). Others have found SIBTEST to be more effective in identifying DIF items (e.g., Bolt, 2002;Jiang & Stout, 1998).…”
Section: Research Questionsmentioning
confidence: 95%
“…We used a nonparametric approach to the assessment of DIF as implemented in the SIBTEST statistical software package (for a technical description of the SIBTEST procedure, see Sheely andStout, 1992a,b andLiang andStout, 1998). SIBTEST estimates respondents' depression levels by counting the number of questions with which respondents agree.…”
Section: Detecting Difmentioning
confidence: 99%